Peran Etos Kerja dan Etika dalam Pengembangan Karir Profesional - Oktavia, Hani; Aulia, Aqilah Rahadatul; Halimah, Hikmah Nur; Alvina, Lydia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to identify and analyze the strategic role of work ethos and work ethics in supporting professional career development in modern organizational environments. Through a qualitative descriptive approach based on a literature study, this research explores various theories, concepts, and previous findings related to the influence of work ethos and work ethics on individual career trajectories and organizational performance. The analysis reveals that work ethos significantly contributes to increasing individual productivity, responsibility, and commitment, while work ethics ensures the integrity, honesty, and fairness of individuals in workplace interactions.The integration of both aspects not only impacts the personal reputation and career opportunities of individuals but also fosters a productive, ethical, and collaborative work environment within organizations. Furthermore, a strong work ethos combined with work ethics encourages trust from superiors, enhances networking opportunities, strengthens leadership potential, and reduces the risk of unethical behavior in the workplace. This condition ultimately leads to greater employee job satisfaction, increased organizational loyalty, and long-term business sustainability. The study concludes that integrating work ethos and work ethics is a vital strategy for sustainable career development and long-term organizational competitiveness. Future research is recommended to empirically test these findings through surveys or case studies in various industrial sectors and to develop value-based career management models tailored to organizational characteristics in Indonesia.